2022
DOI: 10.1186/s40360-022-00586-2
|View full text |Cite
|
Sign up to set email alerts
|

Long-term low-dose exposure of permethrin induces liver and kidney damage in rats

Abstract: Background Permethrin is one of the pyrethroid insecticides, which is widely used in agriculture and public health. Although acute toxicity of the insecticide has been studied, the chronic toxicity upon the long-term exposure has not been clear yet. The purpose of the current study is to investigate the organ toxicities of permethrin following its long-term low-dose exposure. Methods Male Wistar rats were daily administrated orally with permethrin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…This study concurs with the findings of Danaei et al [21] regarding the effect of diazinon on the liver and kidneys of rodents. In addition to what was observed in the case study, similar changes in heterotrophy, degeneration, and swelling were observed in Sun et al [22] investigation on the effect of permethrin on rat liver cells and kidneys.…”
Section: Resultssupporting
confidence: 87%
“…This study concurs with the findings of Danaei et al [21] regarding the effect of diazinon on the liver and kidneys of rodents. In addition to what was observed in the case study, similar changes in heterotrophy, degeneration, and swelling were observed in Sun et al [22] investigation on the effect of permethrin on rat liver cells and kidneys.…”
Section: Resultssupporting
confidence: 87%
“…Similar results were observed when rats were treated with 50 mg.kg -1 b.wt. of cypermethrin orally for six weeks [8].…”
Section: Hematological Parametersmentioning
confidence: 99%
“…Toxicity of insecticides in man, animal and aquatic organism may occur through oral, inhalation and dermal route. Many oral/dermal toxicity studies have been performed for different pyrethroids insecticides in the past by different scientists [5][6][7][8]. Nevertheless, the impact of repeated dermal exposure to permethrin on hemato-biochemistry has not been conducted yet.…”
Section: Introductionmentioning
confidence: 99%
“…Permethrin exposure disrupts the balance of the antioxidant system in non-target organisms and causes oxidative damage to DNA, lipids, and proteins (Weidinger and Kozlov 2015 ). Sun et al ( 2022 ) reported that long-term and low-dose exposure to permethrin caused liver and kidney damages in non-target rats. Davoodi et al ( 2012 ) found that high mortality rates were observed in juvenile Cyprinus carpio treated with permethrin in the dose range of 10–125 mg/L.…”
Section: Introductionmentioning
confidence: 99%